China in Sixteenth-Century Portuguese Nautical Cartography - Oliveira, Francisco Roque de (2022)
Sixteenth-century Portuguese nautical cartography offers a privileged entry point from which to reconstruct the complex process of Europe becoming familiar with China’s geography during the early modern period. This cartography encompasses an unusually numerous and diverse set of maps, which nonetheless also have great internal coherence. This is due to the fact that most of these cartographical specimens incorporate empirical information resulting from successive hydrographic surveys carried out by Portuguese crews who sailed the seas of Asia from the late fifteenth century onward. From then on, the agents of the Portuguese Crown operating in the Indian Ocean region strove to simultaneously gather commercial and geographical information about various areas situated east of Malacca, particularly with regard to insular Southeast Asia and China itself. These were two of the main strategic objectives of Portugal’s imperial policy in Asia during the reign of King Manuel (r. 1495-1521); in one way or another, these objectives endured over the following decades.